ASSESSING THE IMPACT OF TRADE LIBERALIZATION ON ECONOMIC GROWTH: A COMPARATIVE ANALYSIS OF DEVELOPING ECONOMIES IN THE CONTEXT OF GLOBALIZATION AND POLICY IMPLICATIONS - Caroline Caroline; Siti Sumiati; Ahmad Rizani; Loso Judijanto; Yamolala Zega (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
In the context of globalization, this study assessed the impact of trade liberalization on economic growth in developing economies and provided essential policy implications. Utilizing a comparative analysis, historical perspectives, and quantitative measures, we examined case studies of developing nations to understand the dynamic relationship between trade liberalization and economic growth. The results demonstrated that trade liberalization has generally yielded positive outcomes, fostering economic growth and integration into the global economy. Developing countries that actively engaged in trade liberalization experienced increased foreign direct investment, expanded exports, and enhanced economic development. However, the study also identified various factors influencing this relationship, including institutional factors, human capital, investment in infrastructure, and political stability. In the context of globalization, the study highlighted the profound impact of international trade agreements and the need for responsive trade policy reforms. Lessons from the comparative analysis were used to provide practical recommendations for developing economies. These recommendations emphasize the importance of nurturing human capital, promoting sound governance, and investing in critical infrastructure. While acknowledging the potential challenges and risks, this research underlines the significance of carefully crafted trade policies to harness the benefits of trade liberalization and ensure sustainable economic growth.